Transcription Factors and Medium Suitable for Initiating the Differentiation of Human‐Induced Pluripotent Stem Cells to the Hepatocyte Lineage. Issue 9 (2nd February 2016) - Tomizawa, Minoru; Shinozaki, Fuminobu; Motoyoshi, Yasufumi; Sugiyama, Takao; Yamamoto, Shigenori; Ishige, Naoki
ABSTRACT: Transcription factors and culture media were investigated to determine the condition to initiate the differentiation of human‐induced pluripotent stem (iPS) cells most efficiently. The expression of genes in human adult liver was compared with that in 201B7 cells (iPS cells) using cDNA microarray analysis. Episomal plasmids expressing transcription factors were constructed. 201B7 cells were transfected with the episomal plasmids and cultured in ReproFF (feeder‐free media maintaining pluripotency), Leibovitz‐15 (L15), William's E (WE), or Dulbecco's modified Eagle medium/Nutrient F‐12 Ham (DF12) for 7 days. RNA was isolated and subjected to real‐time quantitative PCR to analyze the expression of alpha‐feto protein (AFP) and albumin. cDNA microarray analysis revealed 16 transcription factors that were upregulated in human adult liver relative to that in 201B7 cells. Episomal plasmids expressing these 16 genes were transfected into 201B7 cells. CCAAT/enhancer‐binding protein alpha (CEBPA), CCAAT/enhancer‐binding protein beta (CEBPB), forkhead box A1 (FOXA1), and forkhead box A3 (FOXA3) up‐regulated AFP and down‐regulated Nanog. These four genes were further analyzed. The expression of AFP and albumin was the highest in 201B7 cells transfected with the combination of CEBPA, CEBPB, FOXA1, and FOXA3 and cultured in WE. The combination of CEBPA, CEBPB, FOXA1, and FOXA3 was suitable for 201B7 cells to initiate differentiation to the hepatocyte lineage and WE was the most suitable medium for culture after transfection. J. Cell. Biochem. 117: 2001–2009, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Liver‐specific transcription factors initiated differentiation of human‐induced pluripotent stem cells to hepatocyte lineage in William's E medium.